Rancang Bangun Aplikasi Perpustakaan Online Di SMK Grafika Yayasan Lektur Berbasis Android - Chumaidi; Hendri Andriansyah (CV. Multi Kreasi Media, 2024)
The library is a collection of books and magazines. While a library can be defined as a person's personal collection, it is generally recognized as a large collection that is funded and managed by a city or institution. Secondary school library which serves as an informative function. This is because the system still uses a manual recorder. Most of the collections in the high school library can be borrowed by students, with a predetermined loan period. Restrictions on the length of the borrowing period are enforced, so that the limited number of copies of books can be used optimally by students, but not a few students are late in returning books, causing many books to be held up. This is a distinct loss for secondary schools, because books that are supposed to be learning aids are not used optimally. Besides that, it is also detrimental to students because they cannot borrow the book to study. Therefore an application is needed to maximize the use of books in the library that can send notifications/notifications of borrowing periods.